Stabilization of a CSTR in an oscillatory state by varying the thermal characteristics of the reactor vessel - Razon, Luis F. (Animo Repository, 2006)
One of the most thoroughly studied systems in chemical engineering is the classic problem of a first-order exothermic reaction in a diabatic CSTR. In this paper, an extension of the classic problem, in which the reactor vessel temperature varies independently of its contents, is considered. A bifurcation analysis showed that a CSTR in an oscillatory state may be stabilized by the use of a reactor with the appropriate combination of thermal characteristics. Stabilization of an oscillatory state was demonstrated for a variety of scenarios that had been previously shown by Uppal, Ray and Poore to be representative cases of phase diagrams that exhibit limit-cycle behavior. Copyright © 2006 The Berkeley Electronic Press. All rights reserved.